(untitled) (Revista Contexto & Saúde, 2026)
Objective: to collaboratively build a material with scientific information to promote and maintain the health of the elderly population. Method: this is an action research aimed at the collective construction of educational material. Data collection and construction of educational material was carried out in June 2022, in the city of Paranavaí - Paraná, Brazil. The research consisted of five phases: identification of doubts that permeated the lives of elderly people during the COVID-19 pandemic; content composition; choice of illustrations; evaluation of the material by specialists; and approval of the material by seniors. The elderly were randomly selected from the survey that the nurse of a Basic Health Unit made of the elderly in their area, who had preserved cognitive capacity to respond to the questionnaire. Results: the survey included 15 elderly people and four health professionals who were nurses. Regarding vaccination against Covid-19, 14 elderly people (93.3%) were immunized with three doses of the vaccine and one (6.6%) with two doses. Regarding the search for information about COVID-19, 13 (86.6%) searched through traditional media, such as: radio and television and six (40%) through digital media, such as: YouTube, Instagram, WhatsApp and Facebook, with 10 (66.6%) disseminate the information received about COVID-19 and five (33.3%) do not. Conclusion: it is concluded that there are still many doubts that permeate the lives of the elderly regarding the COVID-19 pandemic, and the construction of the folder is one of the strategies to facilitate access to information related to health, free of Fake News.